The pricing behaviour of firms in the euro area: new survey evidence - Silvia Fabiani; M. Druant; I. Hernando; Claudia Kwapil; B. Landau; C. Loupias; F. Martins; T. Mathä; R. Sabbatini; H. Stahl; A. Stokman (National Bank of Belgium, 2005)
This study investigates the pricing behaviour of firms in the euro area on the basis of surveys conducted by nine Eurosystem national central banks. Overall, more than 11,000 firms participated in the survey. The results are very robust across countries. Firms operate in monopolistically competitive markets, where prices are mostly set following mark-up rules and where price discrimination is a common practice. Our evidence suggests that both time- and state-dependent pricing strategies are applied by firms in the euro area: around one-third of the companies follow mainly time-dependent pricing rules while two-thirds use pricing rules with some element of state-dependence. Although the majority of firms take into account a wide range of information, including past and expected economic developments, about one-third adopts a purely backward-looking behaviour. The pattern of results lends support to the recent wave of estimations of hybrid versions of the New Keynesian Phillips Curve. Price stickiness arises both at the stage when firms review their prices and again when they actually change prices. The most relevant factors underlying price rigidity are customer relationships - as expressed in the theories about explicit and implicit contracts - and thus, are mainly found at the price changing (second) stage of the price adjustment process. Finally, we provide evidence that firms adjust prices asymmetrically in response to shocks, depending on the direction of the adjustment and the source of the shock: while cost shocks have a greater impact when prices have to be raised than when they have to be reduced, reductions in demand are more likely to induce a price change than increases in demand.
Keywords: E30; D40; 330; price setting; nominal rigidity; real rigidity; inflation persistence; survey data.; Preismanagement; Marktstruktur; Eurozone; EU-Staaten